Fluorescent chemodosimeter for quantification of Cystathionine-y-synthase activity in plant extracts and imaging of endogenous biothiols - Agarwalla, Hridesh; Hoskere, Anila A.; Ali, Firoj; Pradhan, Swaraj Rashmi; Ganguly, Bishwajit; Pramanik, Sumit kumar; Das, Amitava (Chemical Communications, 2018)
A new reagent for quantification of CgS in plant extracts using a generalized methodology suitable for recognition of homocysteine (Hcy) with luminescence ON response.

Photoactivatable prodrug for simultaneous release of mertansine and CO along with a BODIPY derivative as a luminescent marker in mitochondria: a proof of concept for NIR image-guided cancer therapy - Tiwari, Rajeshwari; Shinde, Prashant S.; Sreedharan, Sreejesh; Dey, Anik Kumar; Vallis, Katherine A.; Mhaske, Santosh B.; Pramanik, Sumit kumar; Das, Amitava (Chemical Science, 2021)
Controlled and efficient activation is the crucial aspect of designing an effective prodrug. Herein we demonstrate a proof of concept for a light activatable prodrug with desired organelle specificity. Mertansine, a benzoansamacrolide, is an efficient microtubule-targeting compound that binds at or near the vinblastine-binding site in the mitochondrial region to induce mitotic arrest and cell death through apoptosis. Despite its efficacy even in the nanomolar level, this has failed in stage 2 of human clinical trials owing to the lack of drug specificity and the deleterious systemic toxicity. To get around this problem, a recent trend is to develop an antibody-conjugatable maytansinoid with improved tumor/organelle-specificity and lesser systematic toxicity. Endogenous CO is recognized as a regulator of cellular function and for its obligatory role in cell apoptosis. CO blocks the proliferation of cancer cells and effector T cells, and the primary target is reported to be the mitochondria. We report herein a new mitochondria-specific prodrug conjugate (Pro-DC) that undergoes a photocleavage reaction on irradiation with a 400 nm source (1.0 mW cm(-2)) to induce a simultaneous release of the therapeutic components mertansine and CO along with a BODIPY derivative (BODIPY(PPH3)(2)) as a luminescent marker in the mitochondrial matrix. The efficacy of the process is demonstrated using MCF-7 cells and could effectively be visualized by probing the intracellular luminescence of BODIPY(PPH3)(2). This provides a proof-of-concept for designing a prodrug for image-guided combination therapy for mainstream treatment of cancer.